Historical roots and modern realities: Austria's sports ecosystem - Ivana Pranjić; Marko Begović (Frontiers in Sports and Active Living)
IntroductionThis article provides an overview of the sport structure and policies in Austria, offering a comprehensive analysis of existing frameworks and potential future developments. It explores the historical evolution of sport policy, key legislative milestones, institutional structures, and policy paradigms that have shaped the nation's approach to sports governance.MethodsThe study employs document analysis as the primary research methodology, examining regulatory regimes and national policy documents. A historical outline is used to contextualize the evolution of Austrian sport policies, followed by an in-depth review of legal and regulatory frameworks at national and regional levels.ResultsThe analysis highlights the structural composition of the Austrian sport system, identifying key stakeholders, governing bodies, and constituents. The findings reveal the strengths and limitations of the current sport governance model, with particular attention to legislative developments and institutional interactions.DiscussionThe paper discusses emerging trends in Austrian sport policy, potential areas for reform, and the role of innovative approaches in addressing contemporary challenges. The study contributes valuable insights to the discourse on sports governance in Austria and suggests pathways for future policy development.